Predictors of extra care among magnesium sulphate treated eclamptic patients at Muhimbili National Hospital, Tanzania - Shagdara Mohammed S; Muganyizi Projestine S (BMC, 2011)
Abstract Background The inclusion of Magnesium Sulphate (MgSO4) as a gold standard in the treatment of eclampsia has substantially reduced incidences of repeated fits, eclamptic morbidity and deaths. However, despite treatment with MgSO4, a proportion of patients need extra medical/nursing attention and prolonged stay in the intensive care unit (ICU). The literature on the underlying factors for the need of extra care in the MgSO4 era is lacking. This study sought to establish predictors of extra care in ICU among eclamptic patients after treatment with MgSO4 at Muhimbili National Hospital (MNH). Methods Data were obtained from hospital records of eclamptic patients who were admitted at MNH and treated with MgSO4 from January 1st to December 31st, 2008. Based on set criteria, patients who needed extra care were identified. Analysis was performed using PASW statistics 18 whereby frequencies, cross-tabulations, bivariate and multiple logistic regressions were performed. Results A total of 366 eclamptic patients were admitted and treated with MgSO4 at MNH during a 12 month study period in 2008. Most of these (76%) were referred from district hospitals and132 (36%) met the criteria for extra care in ICU. After adjusting for other variables, the risk of extra care in ICU for patients who were admitted with altered consciousness was double (OR = 2.3; 95% CI: 1.3-4.0) that of the ones admitted in alert state. The risk or need of extra care increased by increasing time to delivery and was doubled (OR = 2.0; 95% CI:1.1-3.7) if it was between 12 and 24 hours and tenfold elevated (OR = 10.0; 95% CI:4.3-23.6) if beyond 24 hours as compared to when time to delivery was less than 12 hours. Abdominal delivery was also independently associated with increased risk compared to vaginal delivery (OR = 2.5; 95%CI: 1.4-4.5). The type of referral and number of fits were associated with extra care in ICU but this association was wholly explained by the clinical status of the patient on admission to MNH and prolonged time lag to delivery. Conclusion We concluded that even with MgSO4 used as the gold standard in the treatment of eclampsia, effective pre-referral care and expedited delivery were crucial in minimizing the need for extra care in ICU.